Tuhan dan Hantu dalam Teologi Kejawen: Sebuah Interpretasi Atas Ajaran R.Ng.Ronggowarsito - Wildan Taufiqur Rahman; Yoga Irama (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2022)
Kejawen is often interpreted as harmful, deviant, and far from theological elements. This is inseparable from the mandate that kejawen is synonymous with magical, irrational, and magical things. It is as if there is a demarcation line that separates the two elements, assuming that kejawen is dry with spiritual and theological aspects. However, this research proves that kejawen theology is a theological view that is uniquely Javanese. From kejawen theology, a lot can be extracted about the manifestation of God and other dimensions, including the supernatural, namely ghosts. In addition, kejawen has also become the value of life in Javanese society, full of inner appreciation. And through the interpretation of R.Ng.Ronggowarsito's teachings are contained in the Wirid Hidayat Jati and Paramayoga Fibers; one can get an outline that kejawen is closely related to Islam.